Seasonal abundance of the stable fly Stomoxys calcitrans in southwest England. Issue 4 (30th May 2019) - Parravani, A.; Chivers, C.‐A.; Bell, N.; Long, S.; Burden, F.; Wall, R.
Abstract: The stable fly Stomoxys calcitrans (L.) is a cosmopolitan biting fly of both economic and welfare concern, primarily as a result of its painful bite, which can cause blood loss, discomfort and loss of productivity in livestock. Between June and November in 2016 and May and December in 2017, Alsynite sticky‐traps were deployed at four Donkey Sanctuary sites in southwest England, which experience recurrent seasonal biting fly problems. The aim was to evaluate the seasonal dynamics of the stable fly populations and the risk factors associated with abundance. In total, 19 835 S. calcitrans were trapped during the study period. In both years, abundance increased gradually over summer months, peaking in late August/September. There were no relationships between seasonally detrended abundance and any climatic factors. Fly abundance was significantly different between sites and population size was consistent between years at three of the four sites. The median chronological age, as determined by pteridine analysis of flies caught live when blood‐feeding, was 4.67 days (interquartile range 3.8–6.2 days) in males and 6.79 days (interquartile range 4.8–10.4 days) in females; there was no significant, consistent change in age or age structure over time, suggesting that adult flies emerge continuously over the summer, rather than in discrete age‐related cohorts. The data suggest that flies are more abundant in the vicinity of active animal facilities, although the strong behavioural association between flies and their hosts means that they are less likely to be caught on traps where host availability is high. The implications of these results for fly management are discussed. Abstract : Stable fly abundance, measured over 2 years at four sites in southwest England, increased over the summer, peaking in late August/September. Fly abundance was higher close to animal housing, although a strong local association with hosts resulted in lower catches on traps where host availability was high. A relatively stable population age structure suggests that adult stable flies emerge continuously over the summer.